Comparative efficacy of sleep positional therapy, oral appliance therapy, and CPAP in obstructive sleep apnea: a meta-analysis of mean changes in key outcomes - Yunjun Gao; Sixiang Zhu; Wenjun Li; Youqing Lai (Frontiers in Medicine, 2025)
BackgroundObstructive sleep apnea (OSA) is commonly treated with continuous positive airway pressure (CPAP), though many patients struggle with adherence. Sleep positional therapy (SPT) offers a potential alternative, especially for positional OSA (POSA). This study aimed to compare the efficacy and safety of SPT with CPAP, oral appliance therapy (OAT), and placebo.MethodsNineteen randomized controlled trials (RCTs) with 1,231 participants were included. Data extraction focused on changes in key outcomes such as apnea-hypopnea index (AHI), total sleep time (TST), oxygen desaturation index (ODI), and sleep architecture from pre- to post-intervention. Random-effects meta-analyses were conducted to compare mean changes between SPT and control groups (placebo, OAT, CPAP), with sensitivity analyses to assess heterogeneity.ResultsSleep positional therapy (SPT) showed a significant reduction in AHI in the supine position compared to placebo (MD = −7.46, 95% CI: −11.42, −3.49), although no difference was observed in overall AHI between SPT and placebo or OAT. Compared to CPAP, SPT was less effective in reducing AHI, with a trend toward greater reductions in AHI favoring CPAP. SPT demonstrated a significant improvement in arousal index compared to OAT (MD = −7.11, 95% CI: −10.52, −3.71) and a lower risk of device-related complications compared to both OAT (OR = 0.54, 95% CI: 0.31, 0.95) and CPAP (OR = 0.29, 95% CI: 0.12, 0.72). However, SPT did not lead to significant improvements in TST or oxygen saturation parameters across comparisons.ConclusionSleep positional therapy (SPT) is a safe alternative for managing positional OSA, particularly for patients intolerant to CPAP, though it remains less effective than CPAP in reducing overall AHI and improving oxygenation.